Cultural Heritage and Local Development: Case of Dida (Southwestern of the Republic of Cote d’Ivoire) - Gninin Aicha Toure; Irie Maxime Goeti Bi; Barpougouni Mardjoua (European Scientific Journal, ESJ, 2026)
Established between the 15th and 18th centuries in the region corresponding to present-day Côte d’Ivoire, the Dida community constitutes an exceptional contributor to the enrichment of Ivorian cultural heritage. Its language and traditional attire, on the one hand, together with its craftsmanship and long-standing social practices, on the other, have significantly enhanced the cultural identity of the country over time. Nevertheless, this body of knowledge and cultural wealth is currently under serious threat of disappearance, despite its potential as a driver of development. The objective of this paper is to highlight the contribution of Dida cultural heritage to sustainable and inclusive local development. The methodology combines documentary research and field surveys, complemented by participation in a cultural festival. This integrated approach made it possible to document the breadth of Dida cultural heritage and to analyze its role in fostering local and inclusive development.